Pemodelan Proses Penyusunan Laporan Keberlanjutan pada Usaha Kecil dan Menengah (UKM) - Putu Sukma Kurniawan (Faculty of Economics and Business Mulawarman University, 2017)
Sustainability reporting becomes a new paradigm in corporate reporting. Sustainability reporting demonstrates that management of company have a commitment to engage in business activities, building on the concept of sustainability. This article discusses the implementation of the sustainability reporting on a small and medium enterprises, especially in Indonesia. The discussion is done on the opportunities and challenges of sustainability reporting in small and medium enterprises. Implementation of sustainability reporting in small and medium enterprises adapted to the GRI G4 standard.Keywords: sustainability reporting, sustainability report, small and medium enterprises, GRI G4 standard